THE ANALYSIS OF “DOCTOR STRANGE IN THE MULTIVERSE OF MADNESS” FILM SUBTITLE TRANSLATION - Yozar Firdaus Amrullah; Pratama Irwin Talenta (Jurnal CULTURE (Culture, Language, and Literature Review), 2022)
This article analyzes “Doctor Strange in the Multiverse of Madness” film Subtitle Translation from English into Bahasa Indonesia. Mona Baker’s Translation Strategy is used to find out the equivalency of the meaning of the dialogs at word and idiom level. The data is collected by observation method with free observation technique and record technique. The analysis is conducted through four steps: first, make data list of sentences based on its appearance through time set for the film. Next, identify the English and Bahasa Indonesia translation, then collect the words and idioms of the dialogs which have non-equivalency conditon. Third, evaluate the translation by using Mona Baker’s translation strategy, and last, make conclusion from the data analysis. As the result, the words and idioms translation mostly fulfill Mona Baker’s Translation strategy approach. However, unavoidably there are words and idioms which wrongly translated, then should need correction.